Molecular Detection of Hospital-Acquired and Community-Acquired Staphylococcus Aureus by PCR Amplification of NUC Gene - Qutaiba Dhiaa Hashim, Hadi Rahman Rasheed Al-Taai (Pakistan Journal of Medical & Health Sciences, 2022)
A total of 44 Staphylococcus aureus isolates have been reactivated and diagnosed by using bacteriological and biochemical methods and confirmed by VITEK 2 compact system. The specimens were obtained from several causes included vagina, urine, nose wounds and burns. The results of virulence factors investigation showed that 70.5% of S. aureus isolates were beta hemolytic, 56.8% have Dnase activity, 45.5% were gelatinase positive and 91% were biofilm producer. The results showed a great prevalence of MDR strains of S. aureus with significant p value (<0.001) which were 77.2% while the XDR, PDR and sensitive isolates were 14.6%, 2.2% and 6.8% respectively. Hospital acquired infections caused by S. aureus isolates were the majority in the current study which was 72.72% while the community acquired infections were 27.27% with a significant p value (<0.05). Genetic detection results showed mecA was found in 19 of 24 isolates, whereas the nuc gene was found in 20 of 24 isolates. Keywords: S. aureus, MRSA, nuc, mecA.